Chemotherapeutic Agent Paclitaxel Mediates Priming of NLRP3 Inflammasome Activation - Son, Seunghwan; Shim, Do-Wan; Hwang, Inhwa; Park, Jong-Hwan; Yu, Je-Wook (Frontiers in Immunology, 2019)
Paclitaxel is a chemotherapeutic drug commonly used to treat different types of cancer. In addition to its antitumor effect, paclitaxel is also known to promote Toll-like receptor (TLR) 4-dependent inflammatory responses, which may lower its chemotherapeutic efficacy. However, it remains unclear whether paclitaxel is able to affect inflammasome signaling in myeloid or cancer cells. Therefore, we examined the potential effect of paclitaxel on the activation of an inflammasome complex by examining caspase-1 activation and interleukin (IL)-1bsecretion in bone marrow-derived macrophages (BMDMs). The results showed that treatment with paclitaxel alone or following LPS priming failed to trigger the secretion of active caspase-1 and IL-1bfrom BMDMs. However, paclitaxel could induce robust activation of caspase-1 in BMDMs in the presence of NLRP3 inflammasome-activating signal 2, such as ATP or nigericin. This paclitaxel/ATP-mediated inflammasome activation was completely abrogated in Nlrp3-deficient macrophages. Mechanistically, paclitaxel treatment induced robust activation of the TLR4 signaling cascade, including phosphorylation of IkB and JNK and upregulation of proinflammatory cytokine mRNA levels in a TLR4-dependent manner. In contrast, paclitaxel treatment did not induce mitochondrial damages such as the loss of the mitochondrial membrane potential and production of mitochondrial ROS. These findings suggest that paclitaxel can drive the priming of signal-mediated events for NLRP3 activation but not a second signal-triggered phenomenon such as mitochondrial damage. This suggestion was supported by the observations that paclitaxel treatment caused robust IL-1b production in macrophages in the presence of cell-free medium derived from growth of injured cells and also in the spleen of mice. Collectively, our data strongly indicate that paclitaxel is able to facilitate the activation of NLRP3 inflammasome signaling in a certain physiological environment.